Nilai Pendidikan Islam dalam Pantun Pernikahan Melayu Sambas - Nilda, Nilda (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
The pantun tradition in the Sambas Malay community serves not only as a form of storytelling but also as an educational medium rich in moral and religious values. This study aims to identify and analyze the internalization of Islamic educational values contained in Sambas Malay wedding pantuns. The study used a descriptive qualitative approach with content analysis techniques on wedding pantuns collected through observation and documentation. The results indicate that wedding pantuns contain values such as faith, noble character, responsibility, patience, gratitude, and the importance of maintaining marital harmony. These values are passed down from generation to generation and form part of the formation of Islamic character in the community.